UV Spectrophotometric Determination of Tamsulosin Hydrochloride - GOWRI SANKAR, D.; DURVASA RAO, B.; SAI KISHORE, V.; MURTHY, T.E.G.K. (Asian Journal of Chemistry, 2010)
A UV spectrophotometric method has been developed for the determination of tamsulosin hydrochloride in pure form and pharmaceutical formulations. This method obyes Beer’s law in the concentration range 30-80 μg/mL and exhibiting maximum absorption at 282 nm. This method was extended to pharmaceutical formulations and there is no interference of additives and excepients.